Immunogenicity Monitoring Cell Chip Incorporating Finger-Actuated Microfluidic and Colorimetric Paper-Based Analytical Functions - Lee, Kyung Won; Yang, Eun Kyeong; Oh, Yujeong; Park, Eunhye; Jeong, Kwan Young; Yoon, Hyun C. (Biochip Journal, 2023)
Recently, with the development of microfluidic chips, attempts to integrate cell culture and biomedical material testing functions into a single chip have increased to supplement experimental animal models. Among the evaluations of biomaterials, immunogenicity testing, a current priority, is attracting attention. In this study, we developed a simple and easy-to-handle immunogenicity-testing cell chip to evaluate the immunogenicity of biomaterials. On this chip, macrophages were introduced as immunogenicity indicators, and a micro-paper-based analytical device (µPAD) was used for optical analysis. Macrophages are present in all parts of the body and mediate immune reactions against body implants or bio-derived substances, resulting in the production of hydrogen peroxide. In the cell chamber of the developed cell chip, macrophages grow and react to immunogenic materials. Activated macrophages secrete hydrogen peroxide, which is then transferred to the PAD with single-finger actuation. The hydrogen peroxide molecules reaching the PAD detection zone react with the colorimetric detection substrate, resulting in a color that corresponds to the hydrogen peroxide concentration. With the developed testing chip, the immunogenicity of biomaterials can be determined before administration.
Keywords: Analytical functions; Cell chips; Cell metabolite biosensor; Cell metabolites; Colorimetric sensing; Finger actuation microfluidic chip; Immunogenicity; Immunogenicity monitoring; Microfluidic-chips; Paper-based analytical devices; Cell metabolite biosensor; Colorimetric sensing; Finger actuation microfluidic chip; Immunogenicity monitoring; Paper-based analytical device